2021
DOI: 10.5603/gp.a2021.0092
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-related comorbidities and labor induction — the effectiveness and safety of dinoprostone compared to misoprostol

Abstract: Objectives:The aim of the study was to evaluate whether the presence of the disease in pregnancy influences the effectiveness and safety of delivery preinduction with prostaglandins: misoprostol vaginal insert and dinoprostone vaginal gel. Material and methods:This is a retrospective cohort study conducted of 560 pregnant women.The concomitant diseases mainly recorded were diabetes mellitus, hypertensive diseases, intrahepatic cholestasis of pregnancy, asthma, thrombocytopenia, and hypothyroidism. The 2 primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…From the above data, it is clear that the use of the insert with Misoprostol is characterized by a higher percentage of cesarean sections and reduced time to cesarean delivery (most patients deliver within 24 h). These data are consistent with the results of the research carried out so far [ 21 , 25 , 26 ]. Most patients who received a Dinoprostone insert or Foley catheter delivered within 48 h with Dinoprostone dominance (73.9% and 57.9%).…”
Section: Discussionsupporting
confidence: 93%
“…From the above data, it is clear that the use of the insert with Misoprostol is characterized by a higher percentage of cesarean sections and reduced time to cesarean delivery (most patients deliver within 24 h). These data are consistent with the results of the research carried out so far [ 21 , 25 , 26 ]. Most patients who received a Dinoprostone insert or Foley catheter delivered within 48 h with Dinoprostone dominance (73.9% and 57.9%).…”
Section: Discussionsupporting
confidence: 93%
“…However, quite a few published studies contradict our results. A few authors have concluded that IOL with misoprostol strongly increases the risk of cesarean delivery and leads to prolonged labor [ 32 , 37 , 38 , 39 ]. The differences in results are likely due to differences in study designs.…”
Section: Discussionmentioning
confidence: 99%